2021
DOI: 10.1016/j.vaccine.2021.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine innovation prioritisation strategy: Findings from three country-stakeholder consultations on vaccine product innovations

Abstract: As part of the Vaccine Innovation Prioritisation Strategy (VIPS), three immunization-stakeholder consultations were conducted between September 2018 and February 2020 to ensure that countries’ needs drove the prioritization of vaccine product innovations. All consultations targeted respondents with immunization program experience. They included: (1) an online survey to identify immunization implementation barriers and desired vaccine attributes in three use settings, (2) an online survey to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“… 35 We anticipated vaccine damage due to cold chain failures (freezing or heat exposure) to be a contextual driver of controlled temperature chain demand. While in two surveys, national and global stakeholders saw utility of such approach to avert these problems, 41 , 46 vaccine damage as a driver of demand was only cited in four unique implementations. 16 , 17 , 21 , 34 , 36 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 35 We anticipated vaccine damage due to cold chain failures (freezing or heat exposure) to be a contextual driver of controlled temperature chain demand. While in two surveys, national and global stakeholders saw utility of such approach to avert these problems, 41 , 46 vaccine damage as a driver of demand was only cited in four unique implementations. 16 , 17 , 21 , 34 , 36 …”
Section: Resultsmentioning
confidence: 99%
“…Three surveys indicated that 72% (18/25) to 75% (21/28) of national and global policy-makers showed a demand for controlled temperature chain use. 19 , 41 , 46 Awareness raised through policy adaptations, including WHO endorsement for controlled temperature chain-relevant storage of the HepB birth dose, predicated uptake in two implementations. 20 , 22 Awareness via endorsement from implementation partners was noted to influence uptake by health ministries in oral cholera vaccine and tetanus toxoid-containing vaccine experiences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this issue has been faced in the smallpox global vaccination campaign [ 28 ], it became more evident for the novel mRNA-based vaccines that currently require continuous storage at ultra-cold temperatures, which is not feasible in many parts of the world. The need for thermostable vaccines had already been recognized before the COVID-19 pandemic, for example, in a study by the Vaccine Innovation Prioritization Strategy (VIPS) [ 29 ], in which the ability to withstand heat exposure was identified as the most desired characteristic for vaccines used in outreach and campaign settings by experienced immunization staff. Lack of vaccine thermostability leads to limited or no access to vaccinations by people living in remote areas or low-resource settings.…”
Section: Discussionmentioning
confidence: 99%
“…To improve vaccine administration, VIPS has assessed innovative technologies and conducted stakeholder consultations to develop consensus on what new vaccine technologies are needed to increase coverage. VIPS partners are now accelerating the advancement of selected new technologies [39] , [40] , [41] .…”
Section: Lessons From Covid-19mentioning
confidence: 99%